Institutional mechanisms for promoting accountability in the Philippine Civil Service - Yangco, Mario D. (Asian Review of Public Administration, 1991)
In the Philippine Civil Service, major institutional mechanisms for enforcing accountability in the civil service are in place. Amongst these are enforcement of a code of conduct and ethical standards, personnel inspection and audit, monitoring agency performance appraisal, administrative discipline, the fast track provincialization programme of the Civil Service Commission Service and others.